PENGARUH TINGKAT PENDIDIKAN, PENDAPATAN KELUARGA DAN USIA KAWIN PERTAMA TERHADAP JUMLAH KELAHIRAN DI KELURAHAN LEDEUNU KECAMATAN RAIJUA KABUPATEN SABU RAIJUA - Leo, Rani Asria Buwe; Hasan, Muhammad Husain; Sukmawati, Sukmawati (Jurnal Geografi, 2023)
Birth is the number of babies born to women, there are babies who are called live births, namely the birth of a baby who shows signs of life, can not expected for some time the baby will show these signs of life. The aims of this study are (1) to determine the effect of education level on birth, (2) to determine the effect of family income on birth, (3) to determine the effect of age at first marriage on birth. This research was conducted in Ledeunu Village, Raijua District, Sabu Raijua Regency with a quantitative research type, the sample in this study were 32 women of childbearing couples with a purposive sampling method. Data collection techniques used observation, documentation and questionnaire techniques. The research data processed by Microsoft Excel and analyzed by multiple linear regression methods with the SPSS version 16.0 program. The results showed: (1) The education level has a positive and significant effect on number of births with a significant value of 0.008 < 0.05 (2) The family income has a negative and insignificant effect on number of births with a significant value of 0.166 > 0.05 (3) The age of first marriage has a negative and not significant effect on number of births with a significant value of 0.546 > 0.05.